2017
DOI: 10.1002/ags3.12054
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of laparoscopic distal gastrectomy compared to open distal gastrectomy: A retrospective cohort study based on a nationwide registry database in Japan

Abstract: To clarify the safety profile of laparoscopic distal gastrectomy (LDG) for gastric cancer patients, the short‐term outcome of LDG was compared to that of open distal gastrectomy (ODG) by propensity score matching using data from the Japanese National Clinical Database (NCD). We conducted a retrospective cohort study of patients undergoing distal gastrectomy between January 2012 and December 2013. Using the data for 70 346 patients registered in the NCD, incidences of mortality and morbidities were compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 21 publications
1
53
1
Order By: Relevance
“…In the present survey, although the background of surgical procedures as well as the classification of benign or malignant disease differed between endoscopic and open surgery, PI were less frequent after endoscopic surgery, especially for esophageal surgery, gastrointestinal surgery, colorectal surgery, and cholecystectomy. Previous studies reported similar results regarding endoscopic surgery versus open surgery in esophageal surgery (23.5% vs 46.7%), gastrointestinal surgery (1.0% vs 1.8%‐8.9%), colorectal surgery (7.0%‐11.3% vs 15.7%‐25.0%), and cholecystectomy (0.6%‐5.9% vs 4.9%‐19.9%) . In the present survey, there was no incidence of PI after endoscopic esophageal surgery, although the procedures included only esophageal surgery for benign disease, such as esophageal achalasia, hiatus hernia, and selective vagotomy.…”
Section: Discussionsupporting
confidence: 73%
“…In the present survey, although the background of surgical procedures as well as the classification of benign or malignant disease differed between endoscopic and open surgery, PI were less frequent after endoscopic surgery, especially for esophageal surgery, gastrointestinal surgery, colorectal surgery, and cholecystectomy. Previous studies reported similar results regarding endoscopic surgery versus open surgery in esophageal surgery (23.5% vs 46.7%), gastrointestinal surgery (1.0% vs 1.8%‐8.9%), colorectal surgery (7.0%‐11.3% vs 15.7%‐25.0%), and cholecystectomy (0.6%‐5.9% vs 4.9%‐19.9%) . In the present survey, there was no incidence of PI after endoscopic esophageal surgery, although the procedures included only esophageal surgery for benign disease, such as esophageal achalasia, hiatus hernia, and selective vagotomy.…”
Section: Discussionsupporting
confidence: 73%
“…The laparoscopic approach is a complex procedure compared with open surgery, requiring a specialized surgeon and unit. Recent study based on NCD data in Japan showed the incidence of pancreatic fistula was significantly higher in laparoscopic distal gastrectomy compared to open distal gastrectomy [29,30]. In the current study, the incidence of pancreatic fistula was higher in high-volume hospitals partly because laparoscopic gastrectomy were performed in the high-volume hospitals.…”
Section: Discussionmentioning
confidence: 50%
“…During the two years between January 2012 and December 2013, the laparoscopic approach was selected for 33.6% of the Stage I gastric cancer patients who were treated by total gastrectomy. This percentage is rather low, considering the fact that the laparoscopic approach was selected for as many as 55.4% of patients with Stage I cancer who underwent distal gastrectomy during the same period [25]. This possibly reflected the technical difficulty as well as the fact that only laparoscopic distal gastrectomy for Stage I cancer is currently recommended as an optional standard procedure in the Japanese Gastric Cancer Treatment Guidelines [2].…”
Section: Discussionmentioning
confidence: 99%